Proceedings of the 8th ACM Workshop on Performance Monitoring and Measurement of Heterogeneous Wireless and Wired Networks 2013
DOI: 10.1145/2512840.2512841
|View full text |Cite
|
Sign up to set email alerts
|

IEEE 802.11n dual band access points for boosting the performance of heterogeneous WiFi networks

Abstract: The deployment of IEEE 802.11 WLANs is increasing incredibly. Standardization bodies are working on the new so-called 5G 802.11ac technology. This paper addresses the ability of dual band access points (APs) to support heterogeneous client adapters and applications. A focus is given to the dual band APs performance in different configurations. The goal of the work is to understand the characteristics of 802.11n networks in heterogeneous deployments, to ultimately be able to predict behavior so that network per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In [25], the ability of dual band access points (APs) to support heterogeneous client adapters and applications was studied. After real experimentation, the authors found that dual band routers can be useful as a way to reduce the negative effects of the heterogeneity in the network adapters of the clients.…”
Section: E Managing Heterogeneous 80211 Clientsmentioning
confidence: 99%
“…In [25], the ability of dual band access points (APs) to support heterogeneous client adapters and applications was studied. After real experimentation, the authors found that dual band routers can be useful as a way to reduce the negative effects of the heterogeneity in the network adapters of the clients.…”
Section: E Managing Heterogeneous 80211 Clientsmentioning
confidence: 99%
“…Many works (e.g., [1][2][3][4][5][6][7][8][9]) study different characteristics of WiFi in practice, but still more practical tests and a larger set of experiments are needed. For example, most of the works are focused only on the 2.4 MHz band or only study a reduced set of aspects of the 5GHz band.…”
Section: Introductionmentioning
confidence: 99%